The potential use of O6-Benzylguanine, and O6-Methylguanine for the treatment of Alzheimer's Disease, and T. brucei group trypanosomes infections - Philip G Penketh; Raymond P Baumann; Krishnamurthy Shyam (Annals of Systems Biology - Peertechz Publications, 2022)
Very recently we had published a paper entitled 'The Potential Development Sulfonylhydrazines for the Treatment of Alzheimer's Disease' [1]. Our paper was a development from an observation by others from 1997, where a remarkable remission in Dementia was observed in cancer patients following treatment with the chemotherapeutic agent BCNU (Carmustine, 1,3-Bis(2-chloroethyl)-1-nitrosourea) [2].